ANALISIS PERUBAHAN BUNYI PADA BENTUK MORFEM DALAM TEKS PAMBIWARA - Januar, Arma; Rahmawati, Emilia Alatas Nur (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2025)
AN ANALYSIS OF SOUND CHANGES IN MORPHEMIC FORMS IN THE PAMBIWARA TEXTMorphemes are the smallest units of language that have meaning and cannot be divided or separated into smaller ones. (1) in this study the author used the pambiwara text as material for analyzing changes in word form in morphemes; (2) this research aims to describe the changes in morpheme form in examples of pambiwara texts that the author has found; (3) the method used in this research is qualitative descriptive research by collecting existing data in several journals and online print media and using a document studies approach by studying available documents; (4) the results of the research show that in the example of pambiwara text there are several types of morpheme sound form changes, including sound changes due to krama demands, sound changes due to song teacher demands, sound changes due to wilang teacher demands, sound changes due to literary demands, changes sounds due to gender demands; changes in the form of morpheme sounds are still widely used in pambiwara texts, especially in pambiwara texts that use Javanese.